Klasifikasi Emosi Dasar Tokoh Utama dalam Novel Deathpologize Karya Yoana Dianika: Kajian Psikologi Sastra - Aktrifonia; Artifa Sorraya; Endang Sumarti (Universitas Insan Budi Utomo, 2024)
This research aims to conduct a literary psychology study of the novel entitled Deathpologize. The researcher formulated the problem of how the basic emotional aspects of the main character in the novel Deathpologize deal with the basic emotions of joy, anger, fear and sadness. The aim of this research is to explore the psychological elements contained in the novel and classify the basic emotions of the main character. The research method used is descriptive qualitative, with a novel data source, the novel Deathpologize by Yoana Dianika. The novel Deathpologize by Yoana Dianika was published by the publisher Bhuana Ilmu Popular in 2023 with ISBN 978-623-04-1597-5, 13 cm x 19 cm thick, 240 pages. This research data was analyzed descriptively qualitatively using David's basic emotional classification theory Krech. The results of this research show that the basic emotional classification of the main character in the novel Deathpologize by Yoana Dianika consists of four, namely: joy, anger, fear and sadness. The character Steve has a personality that is easily happy, angry, afraid and sad. The indicators of its emergence are dominated by basic emotions. These basic emotions are synonymous with pleasant feelings, irritability, fear and sadness which tend to be detrimental to oneself and the environment around them. This research contributes to the field of literary psychology studies by revealing how authors use psychological elements to shape characters and stimulate emotional responses in readers.